CORRUPTION ERADICATION COMMISSION (KPK) AS AN ANTI-CORRUPTION DA'WAH MEDIA IN INDONESIA - Satryo Pringgo Sejati; Ahmad Burhan Hakim (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
The Corruption Eradication Commission (KPK) was inaugurated in 2004. Since then, many corruption scandals or cases in Indonesia have been revealed, ranging from billions or trillions of rupiah. Of course, the findings of the KPK have surprised many people, it turns out that corruption is rampant and increasingly rampant in Indonesia. So special measures are needed to be able to reduce the number of corruption cases in Indonesia. As a large country, Indonesia should be able to implement strong laws and not discriminate against handling corruption cases. The KPK as a media for anti-corruption preaching in Indonesia seems to have done its utmost to be able to reduce the number of corruption cases in Indonesia, it just takes time and requires the role of all levels of society. The method in this study uses descriptive qualitative research, describing existing phenomena using representative data such as books, scientific journals, online news and other sources that are considered relevant. Literature studies are also used to support this simple research. The preaching or anti-corruption campaign carried out by the KPK has actually been quite optimal, but it requires the role of many levels of society to be able to produce maximum results. The government, through its power structure, must also be able to encourage the Corruption Eradication Committee (KPK) to be more effective in taking action against corruption cases so that related parties are able to consciously realize a corruption-free Indonesia.